SUMOylation of Alpha-Synuclein Influences on Alpha-Synuclein Aggregation Induced by Methamphetamine - Zhu, Lin-nan; Qiao, Hong-hua; Chen, Ling; Sun, Le-ping; Hui, Jia-liang; Lian, Yong-ling; Xie, Wei-bing; Ding, Jiu-yang; Meng, Yun-le; Zhu, Bo-feng; Qiu, Ping-ming (Frontiers in Cellular Neuroscience, 2018)
Methamphetamine (METH) is an illegal and widely abused psychoactive stimulant. METH abusers are at high risk of neurodegenerative disorders, including Parkinson's disease (PD). Previous studies have demonstrated that METH causes α-syn aggregation in the laboratory animal and human. In this study, exposure to high METH doses increased the expression of alpha-synuclein (α-syn) and the small ubiquitin-related modifier 1 (SUMO-1) in vitro and in vivo. Therefore, we hypothesized that SUMOylation of α-syn is involved in high-dose METH-induced α-syn aggregation. We measured the levels of α-syn SUMOylation and these enzymes involved in the SUMOylation cycle in SH-SY5Y human neuroblastoma cells (SH-SY5Y cells), cultures of C57 BL/6 primary mouse neurons and brain tissues of mice exposed to METH. We also determined the effect of α-syn SUMOylation on α-syn aggregation after METH exposure by overexpressing the key enzyme of SUMOylation cycle or silencing SUMO-1 in vitro. Then, we make introduced mutations in major SUMOylation acceptor sites of α-syn by transfecting a lentivirus containing the sequence of WT α-syn or K96/102R α-syn into SH-SY5Y cells and injecting an adenovirus containing the sequence of WT α-syn or K96/102R α-syn into mouse striatum. Levels of the ubiquitin-proteasome system (UPS)-related makers ubiquitin (Ub) and UbE1, as well as the autophagy-lysosome pathway (ALP)-related markers LC3, P62 and lysosomal associated membrane protein 2A (LAMP2A), were also measured in SH-SY5Y cells transfected with lentivirus and mice injected with adenovirus. The results showed that METH exposure decreases the SUMOylation level of α-syn, although the protein expression levels of α-syn and SUMO-1 are increased. One possible cause is the reduction of UBC9 level. The increase in α-syn SUMOylation by UBC9 overexpression relieves METH-induced α-syn overexpression and aggregation, whereas the decrease in α-syn SUMOylation by SUMO-1 silencing exacerbates the same pathology. Furthermore, mutations in the major SUMOylation acceptor sites of α-syn aggravate α-syn overexpression and aggregation by impairing degradation through the UPS and the ALP in vitro and in vivo. These results suggest that SUMOylation of α-syn plays an essential role in METH-induced α-syn overexpression and aggregation at high doses and may be a suitable target for the treatment of neurodegenerative diseases.